Assessment of knowledge and skills of nursing staff working in a tertiary care hospital of Western Uttar Pradesh - Kariwala, Peeyush; Dixit, Anand Mohan; Jain, Pankaj Kumar; Rani, Vidya; Srivastava, Dhiraj Kumar (Indian Journal of Community Health, 2018)
Background: Nurses are the most vital part of the health system. Having adequate knowledge, awareness and desired clinical skills among them can decrease the risk of infection or complications, can shorten the stay of patients in hospital, decrease the morbidity and mortality of patients and decrease the disease burden.Material & Methods- Nursing staff from the wards of a private tertiary care hospital were interviewed for knowledge and observed for skill assessment. Aim & Objective: To assess the knowledge, skills and practices of nursing staff working in a tertiary care hospital. Results: Knowledge of nurses is good regarding routine investigations, universal precautions, work ethics but poor in pharmacovigilance. Nurses are found to be good having skills in patient care, clinical skills but are poor in practice of biomedical waste management and vital monitoring. Nurses are having good communication with patient &doctors but response time on patients’ call is more.Conclusion: Retraining of nursing staff at regular intervals to upgrade their knowledge regarding universal precautions, work ethics, bio medical waste management and improve upon clinical skills should be made mandatory in a hospital setting.